1986
DOI: 10.1111/j.1365-2125.1986.tb02879.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of enzyme induction on polymorphic sparteine oxidation.

Abstract: The effects of antipyrine (1200 mg day‐1), phenobarbitone (100 mg day‐ 1) and rifampicin (600 mg and 1200 mg day‐1, respectively) administration for 7 days on sparteine metabolism and 6 beta‐ hydroxycortisol excretion were studied in panels of extensive (EM) and poor metaboliser (PM) subjects. Drug metabolism was induced in both EM and PM subjects by antipyrine and rifampicin pretreatment as indicated by increased excretion of 6 beta‐hydroxycortisol. A 30% increase in metabolic clearance of sparteine was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 15 publications
2
40
0
Order By: Relevance
“…Furthermore, it is known that CYP2D6 is not easily induced. Rifampin, which is a strong inducer, decreases plasma levels of CYP2D6 substrates by only approximately 25% (5,11). Our trial showed a decrease in paroxetine AUC 0-24 of 55%.…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, it is known that CYP2D6 is not easily induced. Rifampin, which is a strong inducer, decreases plasma levels of CYP2D6 substrates by only approximately 25% (5,11). Our trial showed a decrease in paroxetine AUC 0-24 of 55%.…”
Section: Discussionmentioning
confidence: 70%
“…(2) (Bax et al, 1981;Brinn et al, 1986;Eichelbaum et al, 1986). This concept of nonadditivity of environmental factors is well recognized by some geneticists who refer to a norm-of-reaction between the environment and the genotype (Suzuki et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…CYP2D6*10 is responsible for the reduced enzyme activity in IMs whereas CYP2D6*4, CYP2D6*5 and CYP2D6*14 are null alleles which encode no enzyme at all. UM (CYP2D6*xN) has a duplication or multiduplication of functional alleles and leads to increase enzymes activity (6)(7)(8). This variation causes variability in patients' outcomes because CYP2D6 had been reported to biotransform tamoxifen into several active metabolites.…”
Section: Introductionmentioning
confidence: 99%